STUDI MUTU BIJI KAKAO FORASTERO YANG DIOLAH DENGAN METODE SIME-CADBURY - Usman Pato; Yusmarini '; Jumar ' (Universitas Riau, 2003)
The effect of various fermentation times on the quality of dried Forastero cacao beans was evaluated. Dataobtained were treated by the analysts of variance followed by a least significant difference test Various fermen-tiition times significantly affected the total acids, weight of 100 of beans, number of mould-infected beans, andthe colour of cacao beans, however no effect of fermentation times on the fermentation index, p H , aroma andtaste of cocoa beans was observed. The higher quality of d ried Forastero cacao beans processed by use of Slnie-Cadbury method was found when raw beans were fermented for 5 d than for 3 or 7 d.